Study Skills for Sports Studies, 1st edition - Magdalinski, Tara (Routledge, 2020)
Starting university can be a daunting prospect, as students come to grips with new ways of working, learning and thinking. Studying sport at university poses particular challenges, with students often engaged in playing or coaching sport alongside their studies and having unconventional working patterns.